Eye Movement Desensitization and Reprocessing Integrative Group Treatment Protocol (EMDR-IGTP) Applied to Caregivers of Patients With Dementia - Passoni, Serena; Curinga, Teresa; Toraldo, Alessio; Berlingeri, Manuela; Fernandez, Isabel; Bottini, Gabriella (Frontiers in Psychology, 2018)
Caregivers of patients with dementia experience high levels of stress and burden, with effects comparable to those of a traumatic event. Eye Movement Desensitization and Reprocessing (EMDR) appear to be effective in recovering post-traumatic stress disorder (PTSD). We aimed at investigating the effectiveness of the Eye Movement Desensitization and Reprocessing Integrative Group Treatment Protocol (EMDR-IGTP) on the “caregiver syndrome”. Forty-four primary caregivers entered the study. They were randomly assigned to either the “immediate” branch, who received the treatment soon after recruitment, or to the “delayed” branch, who received it two months after recruitment. The treatment consisted of eight group sessions (one per week) spanning over two months. Emotional distress was measured before the treatment, immediately after the end of it, and two months later (follow-up), by means of several clinical scales (Impact of Event Scale-Revised, IES-R; Caregiver Needs Assessment, CNA; Caregiver Burden Inventory, CBI; Anxiety and Depression Scale-Reduced Form, AD-R). The “immediate” branch improved significantly more than the “delayed” (control) branch on The Impact of Event Scale-Revised, the Anxiety, and the Depression scales; however, after treatment such an improvement was maintained only in the first scale. The “delayed” branch took less advantage of the treatment, showing significant reduction only on the Depression scale, an effect which disappeared at follow-up. These preliminary results show for the first time that EMDR-IGTP reduces stress-related symptoms, anxiety, and depression in caregivers of patients with dementia. Interestingly, caregivers who were inserted in a waiting list after recruitment showed smaller treatment effects. Larger samples are needed to better interpret such differential clinical profiles.